The Impact of a Sport Mega Event in the Right to Access Public Education: The Case of the Porto Alegre Communities Affected by the 2014 Brazil World Cup. (October 2021) - Graeff, Billy; Ghiggi, Micheli V.; Knijnik, Jorge
This article addresses key issues of sport mega events' social and educational legacies. The rhetoric of the "legacy" of mega events has been imprinted in every bid presented to different countries and cities to influence their decision whether to host or not this type of event. Visible and also intangible effects are often cited as part of the "legacy" packaged to convince host citizens to adhere to the events. In the past few decades, several studies have been questioning the "legacy" rhetoric, presenting data demonstrating that despite the positive outcomes implied in the concept, these events often cause major impacts in the lives of host countries through several dimensions that cannot be painted with a "positive" tone. This study aims to analyze the educational legacies left by the 2014 FIFA World Cup (WC) in Porto Alegre, capital city of the Brazilian Southernmost state of Rio Grande do Sul. We gathered data using participant observation methodology, surveys, and interviews with inhabitants of communities affected by the WC works. Our data reveal that the lives of public schools, students, and families in the region affected by the event were severely disrupted by the WC works without neither the Local Organizing Committee nor the local authorities offering adequate compensation or plan to alleviate these communities' damages. We conclude by arguing that the WC has provoked a negative educational impact over communities that were already socially disadvantaged and most in need of good functioning of their schools.